2016
DOI: 10.5534/wjmh.2016.34.2.110
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Functional Outcomes and Complications Following the Photoselective Vaporization of the Prostate and Monopolar Transurethral Resection of the Prostate

Abstract: PurposeTo perform a systematic review and meta-analysis of randomized controlled trials (RCTs) comparing monopolar transurethral resection of the prostate (MTURP) and photoselective vaporization of the prostate (PVP) in order to provide the most up-to-date and reliable recommendations possible.Materials and MethodsRelevant RCTs were identified from electronic databases for meta-analysis of the surgical outcomes and complications of MTURP and PVP. Meta-analytical comparisons were made using qualitative and quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…This was more pronounced in patients with BPH with DU than in those without DU. (3) In general, the improvements in micturition symptoms, QoL and PVR in the patients with DU were maintained up to 5 years after PV or HoLEP. (4) In patients with BPH with DU, improvements in micturition symptoms and QoL during the long-term period after HoLEP were greater than improvements after PV.…”
Section: Discussionmentioning
confidence: 87%
“…This was more pronounced in patients with BPH with DU than in those without DU. (3) In general, the improvements in micturition symptoms, QoL and PVR in the patients with DU were maintained up to 5 years after PV or HoLEP. (4) In patients with BPH with DU, improvements in micturition symptoms and QoL during the long-term period after HoLEP were greater than improvements after PV.…”
Section: Discussionmentioning
confidence: 87%
“…This evidence underscores the usefulness of evaluating goal achievement in helping patients to develop realistic treatment expectations and increasing treatment satisfaction. Nevertheless, to date, most studies that have evaluated treatment outcomes of medical or surgical therapies for LUTS/BPH have used traditional outcome measures rather than the tools to assess patient goal attainment [ 18 20 ]. The traditional outcome measures cannot recognize that individual patients perceive their bothersome symptoms and their specific goals or treatment responses differ.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have studied changes in erectile function after PVP, but they have not reached a conclusion about the effect of PVP on erectile function [ 7 8 9 10 11 12 13 14 ]. As mentioned earlier, Paick et al [ 7 ] reported that sexual functioning improved after 6 months following treatment with 80-W potassium-titanyl-phosphate (KTP) PVP.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have reported that medical therapy for ED or BPH could each influence the other [ 5 6 ]. From the surgeon's point of view, the idea that surgical treatment for BPH might affect ED is a focus of current research [ 7 8 9 10 11 12 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation